KONSTRUKSI, BIAS, DAN REKONSTRUKSI GENDER DALAM PENDIDIKAN ISLAM UNTUK MEWUJUDKAN PENDIDIKAN YANG RESPONSIF GENDER - Laili Sulistiana; Era Mutiara Pertiwi; Gazi Saloom; Fathurrahman Muhtar; Ismailthoib (cendekia citra gemilang, 2026)
Gender equality in education is a central agenda within the Sustainable Development Goals (SDGs), particularly in ensuring inclusive and equitable quality education. However, significant challenges persist, especially in developing countries, where social norms, cultural structures, and unequal access continue to shape gender disparities. In the context of Islamic education, gender issues become more complex due to the interaction between religious texts, interpretations, and socio-cultural practices. This study aims to analyze the construction of gender concepts in Islamic education, identify forms of gender bias, and explore strategies for developing gender-responsive Islamic education. This research employs a qualitative approach based on library research, collecting data from scholarly literature, including books, journal articles, and policy documents. Data were analyzed using content analysis in stages: categorization, interpretation, and synthesis. The findings reveal that gender construction in Islamic education is not solely derived from normative religious texts but is significantly influenced by socio-cultural contexts, resulting in dualistic gender roles. Gender bias manifests in curricula, pedagogical practices, and institutional structures, often in both explicit and implicit forms. Despite these challenges, there is a growing transformation toward more inclusive practices, although it remains non-linear and faces cultural and ideological resistance. This study proposes an integrative reconstruction model of Islamic education based on three dimensions: theological reinterpretation, pedagogical transformation, and institutional reform. This model offers a comprehensive framework for promoting gender-equitable and inclusive Islamic education.